Влияние структуры наплавленного материала на прочность и долговечность деталей машин - Березняков, А. И.; Градыский, Юрий Александрович; Стадниченко, Н. Г. (НТУ "ХПИ", 2003)
The influence of precipitation surface's temperature and the speed of surfacing cooling in the process of material's electromagnetic buiding-up on the fatigue durability and tribomechanical characteristics of the restoration surface were examined. The equation connecting the production of entropy with the speed of material cooling was reached. It was established by the way of experiment that materials thermomagnetic machining leads to the improvement of its structure. It is discovered that details restoration by electromagnetic method leads to the improvement of the structure and tribomechanical properties of the surface
Keywords: машиностроение; поверхностное упрочнение; электромагнитная наплавка; ферромагнитный материал; магнитострикция